On the origin of domestic and international terrorism - Krisztina Kis-Katos; Helge Liebert; Günther G. Schulze (University of Freiburg, Department of International Economic Policy (iep), 2010)
We analyze the determinants of the origin of domestic and international terrorism in a large panel data set of 159 countries spanning from 1970 to 2007. We show that terror increases with GDP per capita, a higher POLITY score measuring a more open and competitive political system and experiences of domestic conflict, anarchy and regime transitions. Our evidence thus contradicts the notion that terrorism is rooted in economic deprivation or that strongly autocratic regimes breed more terrorists. Rather we show that weak or failing states are a hotbed for terrorism. Lastly, we show that domestic terror is determined by similar forces as international terror.
Keywords: 330; terrorism; origin of terrorism; negative binomial panel